ENSAIO VISANDO O CONTROLE DAS PRAGAS DA PARTE AÉREA DA BATATINHA COM CARBOFURAN - Rocha, Miguel Antonio Loyola da; Santos, Honório Roberto dos; Zanon, José Inácio; Perri, Antonio Roberto; Silva, Cesar Borges da (REVISTA DE AGRICULTURA, 2020)
ENSAIO VISANDO O CONTROLE DAS PRAGAS DA PARTE AÉREA DA BATATINHA COM CARBOFURAN